Photoactivity and Stability Co-Enhancement: When Localized Plasmons Meet Oxygen Vacancies in MgO - Liu, Z.; Lu, Z.; Bosman, M.; Li, N.; Frankcombe, T.; Jia, Guohua; Tricoli, A.; Liu, Y.; Du, Y.; Yin, Z. (Wiley, 2018)
Durability is still one of the key obstacles for the further development of photocatalytic energy-conversion systems, especially low-dimensional ones. Encouragingly, recent studies show that nanoinsulators such as SiO2 and MgO exhibit substantially enhanced photocatalytic durability than the typical semiconductor p25 TiO2. Extending this knowledge, MgO–Au plasmonic defect nanosystems are developed that combine the stable photoactivity from MgO surface defects with energy-focusing plasmonics from Au nanoparticles (NPs), where Au NPs are anchored onto monodispersed MgO nanotemplates. Theoretical calculations reveal that the midgap defect (MGD) states in MgO are generated by oxygen vacancies, which provide the main avenues for upward electron transitions under photoexcitation. These electrons drive stable proton photoreduction to H2 gas via water splitting. A synergistic interaction between Au's localized plasmons and MgO's oxygen vacancies is observed here, which enhances MgO's photoactivity and stability simultaneously. Such co-enhancement is attributed to the stable longitudinal-plasmon-free Au NPs, which provide robust hot electrons capable of overcoming the interband transition barrier (˜1.8 eV) to reach proton reduction potential for H2 generation. The demonstrated plasmonic defect nanosystems are expected to open a new avenue for developing highly endurable photoredox systems for the integration of multifunctionalities in energy conversion, environmental decontamination, and climate change mitigation.